2016
DOI: 10.1016/j.theriogenology.2016.04.075
|View full text |Cite
|
Sign up to set email alerts
|

Hematocrit changes in healthy periparturient bitches that underwent elective cesarean section

Abstract: Haematocrits were measured before each of 406 caesarean sections performed on 324 bitches at term and again following crystalloid fluid therapy administered at 35 ml/kg over 1½ to 2 h starting from induction. The mean haematocrit was 44.2% (95% CI 43.8 to 44.6%) before caesarean section and 37.8% (95% CI 37.3 to 38.2%) following caesarean section and fluid therapy, with a mean decrease of 6.4 percentage points (95% CI 6.1 to 6.7%) over all 406 caesarean sections. These results provide the clinician with clear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 19 publications
2
21
1
1
Order By: Relevance
“…In a recent large-scale study (De Cramer et al, 2016), mean Ht values measured before elective Caesarean section were in the lower reference range (44.2 ± 4.2%), which is similar to our result (45.3 ± 5.9%). The authors (De Cramer et al, 2016) excluded dehydration by clinical examination and found that only ten of the 406 cases (2.5%) had Ht below 37%. In our study on a smaller number of bitches, 14% of the dogs had lower than 37% but higher than 30% Ht values, which is still less severe than the 30% decrease in Ht described in late pregnant bitches (Tietz et al, 1967).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In a recent large-scale study (De Cramer et al, 2016), mean Ht values measured before elective Caesarean section were in the lower reference range (44.2 ± 4.2%), which is similar to our result (45.3 ± 5.9%). The authors (De Cramer et al, 2016) excluded dehydration by clinical examination and found that only ten of the 406 cases (2.5%) had Ht below 37%. In our study on a smaller number of bitches, 14% of the dogs had lower than 37% but higher than 30% Ht values, which is still less severe than the 30% decrease in Ht described in late pregnant bitches (Tietz et al, 1967).…”
Section: Discussionsupporting
confidence: 92%
“…This common finding in pregnant dogs (Concannon, ; Doxey, ; Tietz et al., ) is known under the term of pregnancy‐associated anaemia (Verstegen‐Onclin & Verstegen, ) and is due to disproportion between erythrocyte volume and the gestation‐induced increased plasmatic volume (Concannon, ; Verstegen‐Onclin & Verstegen, ). In a recent large‐scale study (De Cramer et al., ), mean Ht values measured before elective Caesarean section were in the lower reference range (44.2 ± 4.2%), which is similar to our result (45.3 ± 5.9%). The authors (De Cramer et al., ) excluded dehydration by clinical examination and found that only ten of the 406 cases (2.5%) had Ht below 37%.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Most commonly, PRA has been reported to develop during later pregnancy stages, [4][5][6][7] whereas 2 studies either failed to document preparturition anemia or had reported statistically significant, albeit clinically insignificant, hematocrit decrease during pregnancy. 8,9 Several mechanisms jointly contribute to the development of PRA in women. Hemodilution from volume expansion is a physiological process that causes mild anemia, peaking in women at 20-24 weeks of gestation.…”
Section: Introductionmentioning
confidence: 99%